2021
DOI: 10.7554/elife.65279
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide ACP facilitates lipid oxidation and utilization during long-term flight in locusts

Abstract: Long-term flight depends heavily on intensive energy metabolism in animals; however, the neuroendocrine mechanisms underlying efficient substrate utilization remain elusive. Here, we report that the adipokinetic hormone/corazonin-related peptide (ACP) can facilitate muscle lipid utilization in a famous long-term migratory flighting species, Locusta migratoria. By peptidomic analysis and RNAi screening, we identified brain-derived ACP as a key flight-related neuropeptide. ACP gene expression increased notably u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…After previously having shown that ACP is quickly upregulated when solitary nymphs are crowded, and thus transition to the gregarious phase (Hou et al, 2017), Hou and colleagues showed that the actions of this peptide on flight muscle is essential for both preparing and maintaining long distance flight in this species (Hou et al, 2021). It is worth recalling the partial characterized allatotropin from Locusta, as its description fits ACP remarkably well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After previously having shown that ACP is quickly upregulated when solitary nymphs are crowded, and thus transition to the gregarious phase (Hou et al, 2017), Hou and colleagues showed that the actions of this peptide on flight muscle is essential for both preparing and maintaining long distance flight in this species (Hou et al, 2021). It is worth recalling the partial characterized allatotropin from Locusta, as its description fits ACP remarkably well.…”
Section: Discussionmentioning
confidence: 97%
“…6), thus confirming the specificity of the ACP antiserum. These cells were very recently also described using a rabbit antiserum to ACP (Hou et al, 2021). The data obtained for the expression of these four Locusta neuropeptide genes, calcitonins A and B, ACP and PDF, are summarized in Table 2.…”
Section: Antiserum Specificity Problems and Solutionsmentioning
confidence: 99%
“…AKHs, which are generated from the corpora cardiac, modulate fat body lipid mobilization through Ca 2+ signaling, and finally activate triacylglycerol lipase, which catalyze triacylglycerol into the transport form 1,2-diacylglycerol during prolonged flight ( Van der Horst, 2003 ). A recent study reported that the AKH/corazonin-related peptide can facilitate muscle lipid utilization through promoting fatty-acid-binding protein production in flight muscles of locusts ( Hou et al, 2021 ). In the current study, the reduction in Hif-1α2 extensively repressed the gene expression levels of glycolytic enzymes even in normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The flight treatment is performed using computerized flight mills which have been applied in many published papers ( Du et al, 2022 ; Hou et al, 2021 ). The horizontal arm of the flight mill was made of 1.5 mm plastic stick.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolism of energy substances in insects is regulated by a variety of neuropeptide hormones such as insulin-like hormones, AKH, AKH/corazonin-related neuropeptide (ACP), and octopamine (OA) [ 12 , 14 , 107 , 124 , 153 ]. Among them, insect insulin-like hormones can promote the absorption of glucose and the conversion of glucose into glycogen, inhibit gluconeogenesis, promote the synthesis reaction of proteins and fatty acids, and inhibit the decomposition reaction [ 13 , 154 ].…”
Section: Energy and Substance Metabolism During Insect Migration Flightmentioning
confidence: 99%